Biogeochemistry of dissolved carbon, major, and trace elements during spring flood periods on the Ob River. Issue 11 (25th March 2019) - Vorobyev, Sergey N.; Pokrovsky, Oleg S.; Kolesnichenko, Larisa G.; Manasypov, Rinat M.; Shirokova, Liudmila S.; Karlsson, Jan; Kirpotin, Sergey N.
Abstract: Detailed knowledge of the flood period of Arctic rivers remains one of the few factors impeding rigorous prediction of the effect of climate change on carbon and related element fluxes from the land to the Arctic Ocean. In order to test the temporal and spatial variability of element concentration in the Ob River (western Siberia) water during flood period and to quantify the contribution of spring flood period to the annual element export, we sampled the main channel year round in 2014–2017 for dissolved C, major, and trace element concentrations. We revealed high stability (approximately ≤10% relative variation) of dissolved C, major, and trace element concentrations in the Ob River during spring flood period over a 1‐km section of the river channel and over 3 days continuous monitoring (3‐hr frequency). We identified two groups of elements with contrasting relationship to discharge: (a) DIC and soluble elements (Cl, SO4, Li, B, Na, Mg, Ca, P, V, Cr, Mn, As, Rb, Sr, Mo, Ba, W, and U) negatively correlated ( p  < 0.05) with discharge and exhibited minimal concentrations during spring flood and autumn high flow and (b) DOC and particle‐reactive elements (Al, Fe, Ti, Y, Zr, Nb, Cs, REEs, Hf, Tl, Pb, and Th), some nutrients (K), and metalloids (Ge, Sb, and Te), positively correlated ( p  < 0.05) with discharge and showed the highest concentrations during spring flood. We attribute the decreased concentration of soluble elements with discharge to dilution by groundwater feeding and increased concentration of DOC and particle‐reactive metals with discharge to leaching from surface soil, plant litter, and suspended particles. Overall, the present study provides first‐order assessment of fluxes of major and trace elements in the middle course of the Ob River, reveals their high temporal and spatial stability, and characterizes the mechanism of river water chemical composition acquisition.